Differentiating Diamonds: Transforming Knowledge and the Accumulation of De Beers - David Troy Cochrane (Forum on Capital As Power - Toward a New Cosmology of Capitalism, 2017)
In 1939, the De Beers diamond company faced a dire situation. The company's accumulation had been dwindling for decades. The Great Depression not only pushed diamond sales to historic lows, it shifted American attitudes around consumption and thriftiness to the detriment of the luxury object. In this article, I bring together Liz McFall's assertion that advertising needs to be studied as a “specific commercial device” with Jonathan Nitzan and Shimshon Bichler's capitalas-power theory of value (CasP), which emphasizes differential accumulation. Both McFall and CasP challenge analyses that treat capitalism as an undifferentiated totality. It is from this perspective of differentiated commercial struggle that I analyze De Beers' early advertising campaigns as well as the market research by N.W. Ayer that preceded them. My analysis focuses on an educational component intended to transform the diamond knowledge of the masses. The analysis demonstrates how the research informed the campaign that emerged in contingent relation with various facets of American society and was transformed by changes emergent with WWII.
Keywords: 330; advertising; De Beers; diamonds; differential accumulation; mass consumption